How decisions get made : What is the difference between a decisive leader and an impulsive one? : What is the best way to confront problems within a team? (MIT Sloan Management Review, 2018)
"How do you decide how to decide? What are the best strategies for problem-solving? This collection of articles from MIT Sloan Management Review explores the critical importance of knowing what problem you are trying to solve, taking the time to thoroughly frame a decision and explore the full scope of options, and recognizing that consensus isn't always the best policy."--Resource description page